THE USE OF A MAGNETIC SENSOR TO DETECT LOBSTER (Panulirus spp.) CATCHES ON THE LABORATORY SCALE - Wahyudi, Andri; Hermawan, Maman; Triyono, Heri (Politeknik Kelautan dan Perikanan Sidoarjo, 2023)
Problems in operating trap fish tool are that fishermen do not know the actual condition of the traps. Thus, it causes the effectiveness of time and number of catches to be not optimal. Based on the conditions and problems above, the writer concluded that an innovation in the operation of the trap to design a magnetic sensor-based system/tool to detect lobster catches that can be accessed via smartphone is required. The aim of this study is to design and observe the performance of using a magnetic sensor to detect lobsters' (Panulirus spp.) movements on a laboratory scale (in the aquarium). Data analysis in this study used the Confusion Matrix method, where this method divides the test results into 4 common conditions: TP (True Positive), TN (True Negative), FP (False Positive), and FN (False Negative). From the 4 conditions, Recall, Specificity, Precision, Accuracy, and F1 Score can be calculated. From 16 tests with the 16 lobsters of 60-190 grams/individual, it obtained conditions of TP of 25 times, TN of 109 times, FP of 11 times, and FN of 15 times. From the four conditions, it was obtained a Recall value of 0.625 or 62.50%, Specificity of 0.9083 or 90.83%, Precision of 0.6944 or 69.44%, Accuracy of 0.8375 or 83.75%, and F1 Score of 0.6579 or 65.79%. Based on the observations and test results of the actual detection and application system in this study, performance reference for using magnetic sensors was by using Accuracy with a score of 83.75%.